Evidence of Toxoplasma gondii Exposure in Boer Goat Herds in Missouri, USA. (20th November 2013) - Yaglom, H. D.; Rottinghaus, A. A.; Pithua, P.
Summary Limited data currently exist on the prevalence of Toxoplasma infections in goats in the USA. The objective of this pilot investigation was to determine the prevalence of Toxoplasma gondii antibodies in Boer goats raised in Missouri. Sera collected from 367 Boer goats in 24 herds were tested using a commercial latex agglutination assay. Evidence of T. gondii antibodies was present in 25 of the 367 goats, with titres of 1 : 32 in 4, 1 : 64 in 11, 1 : 128 in 5, 1 : 256 in 3 and 1 : 1024 in 2. Estimates for the apparent animal‐level and between‐herd prevalence were 6.8% (95% CI = 4.7–9.9%) and 41.7% (95% CI = 24.5–61.2%). These results confirm that Boer goats in Missouri are exposed to T. gondii and may constitute a public health risks.